Implikasi Hukum Terhadap Artificial dalam Sistem Peradilan di Indonesia - Karmila, Karmila; Setiawati, Setiawati (Kajian Ilmiah Hukum dan Kenegaraan, 2024)
Purpose: This study aims to analyze the legal impact of Artificial Intelligence (AI) in the Indonesian justice system, focusing on regulations, legal responsibilities, and the ethical and justice-related aspects of its application. Methodology/approach: The research adopts a normative legal method through literature review, examining legislation, Supreme Court policies (such as Smart Assembly and e-Court), legal journals, and relevant news from 2023 to 2025. The focus is on how AI is implemented in the Indonesian judiciary, particularly concerning regulation, ethics, and accountability. Results/findings: The study finds that AI enhances the speed, efficiency, and transparency of judicial processes. Tools like Smart Assembly help objectively assign judges to cases. However, the absence of specific regulations creates ambiguity in assigning legal responsibility for AI-related errors. Additionally, without strict oversight, AI may cause bias, injustice, or human rights violations due to skewed or incomplete training data. Conclusions: AI contributes positively to efficiency and objectivity in Indonesia’s justice system but cannot replace human moral and ethical reasoning. It should be used as a support tool, with final decisions remaining in human hands. This requires adaptive legal frameworks, ongoing supervision, and the application of the human-in-the-loop principle. Limitations: The study is limited to normative analysis and literature review without empirical research or field interviews. It does not assess AI implementation comprehensively across Indonesia. Contribution: This study offers input for regulators in drafting AI-related legal policies and supports the Supreme Court in developing fair AI systems. It also contributes to academic discourse in law, ethics, information technology, and public policy.